Gerontology across the professions and the Atlantic: Development and evaluation of an interprofessional and international course on aging and health. Issue 2 (3rd April 2017) - Clark, Phillip G.; Weeks, Lori E.; van Den Bergh, Graziella; Doucet, Shelley
ABSTRACT: The need for interprofessional teamwork and the global challenges for health care systems of dramatically increasing numbers of older adults have received increased recognition in gerontological and geriatrics education. The authors report on the pilot development of a hybrid course on aging and health for graduate-level health professions students from Norway, Canada, and the United States. International faculty from partnering universities developed, taught, and evaluated the course. Course assignments included online forum postings, reflections, and a problem-based learning group assignment and presentation. Directed readings and discussion included topics related to health care systems and services in the three participating countries, teamwork, and patient-centered care. To evaluate the course, quantitative and qualitative data were collected and analyzed. Results indicate a significant impact on student learning outcomes, including understanding of issues in international aging and health, attitudes and skills in teamwork, and application to clinical practice. This course clearly established the importance of developing innovative interprofessional educational experiences that respond to the increasingly universal impacts of aging populations on health and social care systems around the world.